Adaptive-clustered image-block hierarchical DCT hybrid digital-analog wireless transmission method - Shu TANG; Peng YANG; Xianzhong XIE; Guangyi ZHOU; Jiaqing LI; Yu ZHAO (Tongxin xuebao)
In order to achieve high quality image transmission, a novel hybrid digital-analog (HDA) wireless transmission method was proposed.Firstly, the image residual layer was constructed by subtracting the downsampled and upsampled images from the original image respectively.Secondly, an adaptive-clustered block-level discrete cosine transform (DCT) algorithm was proposed to efficiently remove the correlation between image pixels in the residual layer.Finally, an image block level-based unequal power allocation strategy for further boosting the quality of received images was proposed.Extensive experiments results demonstrate that the proposed method is significantly superior to existing successful hybrid digital analog image wireless transmission methods in both qualitative evaluation and quantitative measurement.